Will forests remain in the face of oil palm expansion? Simulating change in Malinau, Indonesia - Sandker, M.; Suwarno, A.; Campbell, Bruce M. (2007)
The severe tensions between conservation and development are illustrated by events in Malinau District (Kalimantan, Indonesia). Conservationists decry proposed plans for logging and conversion of pristine tropical forest to oil palm (Elaeis guineensis). Although the local government is willing to declare the district a “conservation district,” at the same time, it shows interest in oil palm conversion. This article explores the impact of the potential conversion of 500 000 ha of forest to oil palm on forest cover, in-migration, and the local economy in Malinau. The simulation model was developed using STELLA® software, and relies on a combination of empirical data, data from the literature, and stakeholder perceptions. If a company were to clear the forest for timber without planting oil palm (as commonly happens), poverty levels are likely to rise rather than decline over the long term. If large-scale oil palm plantations were to be established, they could yield significant benefits to local authorities. However, such development would induce massive employment-driven migration, with wide-ranging consequences for the current inhabitants of the region. By visualizing and quantifying these trade-offs between conservation and development, the model stimulates debate and information exchange among conservationists, development actors, and district authorities so that well-informed choices can be made.